The Influence of Organizational Culture and Self-Efficacy on Employee Performance with Work Motivation - Dwi Gemina; Tini Kartini; Vira Sulistiawati (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aimed to assess the impact of self-efficacy and organizational culture on employee performance using work motivation. Methodology/approach: This study used a quantitative approach. The verification and descriptive aspects of this study were its defining features. Data were acquired through extensive literature searches and empirical field research. Results: This study illustrates the connection between improved employee performance, a robust organizational culture, elevated self-efficacy, and a keen interest in their roles. Employee performance is meaningfully impacted by organizational culture and self-efficacy, both directly and indirectly, via the mediating effect of work motivation. Conclusions: Work motivation is how organizational culture and self-efficacy affect employee performance. Limitations: The research results can only be extended to the workforce of PT. Ahli Elektrik Indonesia. Respondents may unintentionally develop subjective prejudices due to the way questionnaires are administered. The influence of other external factors that may affect employee performance was not considered in this study. Contributions: The staff of PT. Ahli Elektrik Indonesia were the focus of this study. Additionally, this study adds to the body of knowledge about employee performance research and attempts to identify the elements that influence employee performance at PT. Ahli Elektrik Indonesia that deserve attention.